Progress in the Field of Sustainable Development as a Result of Implementing the Potential of Social Cohesion: Regional Context - Mykhailenko, Daria; Havrylchenko, Olena; Bezkorovaina, Lidiia; Gliebova, Nataliia; Kovalova, Viktoriia Kovalova (Problemy Ekorozwoju, 2024)
The study examines the role of social cohesion in the context of sustainable development of regional societies. It is proved that progress in the field of sustainable development depends on social cohesion as one of the factors ensuring the achievement of environmental, economic and social changes. A mechanism of social cohesion has been developed, the result of which, along with social stability and justice, strengthening citizens' trust in state and public institutions, social welfare, is a request for sustainable development of regions. The article proves that modern challenges, such as social inequality, migration and ethnic differences, can weaken the potential of social cohesion as a catalyst for sustainable development of regions. To quantify the level of social cohesion, a system of indicators is proposed that integrates economic, demographic, educational and other indicators, and allows for a detailed analysis of the current state of social cohesion in various regions. Taking into account the impact of social cohesion indicators on the progress of sustainable development of regions is realised through the inclusion of indicators that reflect the level of social cohesion potential and, at the same time, are a source of data for assessing the achievement of sustainable development goals. Using the example of the EU countries, the analysis of indicators related to the blocks of trust in institutions and economic indicators in assessing the level of social cohesion was carried out. The estimated indicators are also taken into account when calculating the achievement of the following Sustainable Development Goals (SDGS): SDG 1, SDG 8, SDG 10, SDG 16. The proposed approach makes it possible to take into account the indicators that are most vulnerable in terms of their impact on the progress of regions in the field of sustainable development, as well as to form a list of measures, the implementation of which will ensure capacity building of the social cohesion mechanism (hereinafter referred to as SCM). The main innovative contribution of the study is the development of an economic and mathematical model for optimizing resources and prioritizing measures aimed at strengthening social cohesion. The model takes into account the amount of available resources, the need to use them for the implementation of specific activities and an expert assessment of their priority. This approach provides an objective and systematic solution to the challenges of sustainable development, focusing on social cohesion as a key factor. The study proves that the application of the model requires high-quality data, competence in the process of interpreting modelling results and active interaction with stakeholders. In conclusion, it is emphasized that the integration of social cohesion into strategic planning and the application of the proposed model are the basis for more effective and sustainable development of regional society.